ANALISIS KEMAMPUAN IONISASI GAS H2, D2, DAN He PADA SUMBER ION MUL TICUSP - Kasmudin Kasmudin (BATAN, 2010)
ANAL YSIS OF H2, D2, AND He IONISA TION PERFORMANCE IN THE MUL TICUSP ION SOURCE. To evaluate the performance of the multicusp ion source, an analysis has been carried out which included the study of the performance of the cathode in supplying electrons, the performance of the anode in pulling the electrons from the cathode filament, the magnitude of the electrons kinetic energy during their collisions with gas particles to ionize the particles, the performance of the magnetic field to confine the electrons inside the ionizing chamber, as well as the rate at which ions are produced. The ion-source consists of a gas inlet system, an ion generating system, an ion beam focusing system, a vacuum system, and power supplies. The results showed that the ion source is capable of generating proton or deuteron at a density of 3.6 x 1016 ionsl(cm3.s) and alpha particles at a density of 1.35 x 1016 alphal(cm3.s).